Revealing misfit dislocations in InAsxP1−x-InP core–shell nanowires by x-ray diffraction. (27th September 2019) - Lazarev, Sergey; Göransson, David J O; Borgström, Magnus; Messing, Maria E; Xu, H Q; Dzhigaev, Dmitry; Yefanov, Oleksandr M; Bauer, Sondes; Baumbach, Tilo; Feidenhans'l, Robert; Samuelson, Lars; Vartanyants, Ivan A
Abstract: InAs x P1− x nanowires are promising building blocks for future optoelectronic devices and nanoelectronics. Their structure may vary from nanowire to nanowire, which may influence their average optoelectronic properties. Therefore, it is highly important for their applications to know the average properties of an ensemble of the nanowires. Structural properties of the InAs x P1− x -InP core–shell nanowires were investigated using the coplanar x-ray diffraction performed at a synchrotron facility. Studies of series of symmetric and asymmetric x-ray Bragg reflections allowed us to determine the 26% ± 3% of As chemical composition in the InAs x P1− x core, core–shell relaxation, and the average tilt of the nanowires with respect to the substrate normal. Based on the x-ray diffraction, scanning, and transmission electron microscopy measurements, a model of the core–shell relaxation was proposed. Partial relaxation of the core was attributed to misfit dislocations formed at the core–shell interface and their linear density was estimated to be 3.3 ± 0.3 × 10 4 cm −1 .